The interior urbanism theory reader - Marinic, Gregory (Abingdon, Oxon : Routledge, 2024)
"The Interior Urbanism Theory Reader expands our understanding of urbanism, interiority, and publicness from a global perspective across time and cultures. Interior urbanism is a socio-spatial condition that blurs outdoor and indoor space. Surveying aspects from ancient origins to speculative potentials-architectural, infrastructural, planned, incremental, and adapted-this book explores interior urbanism through an interdisciplinary lens. Fifty chapters investigate the topic in relation to architecture, planning, urban design, interior architecture, interior design, archaeology, engineering, sociology, psychology, and geography. Individual essays reveal the historical, morphological, and typological origins of interior urbanism, as well as its diverse scales, occupancies, and atmospheres. The Interior Urbanism Theory Reader will appeal to scholars, practitioners, students, and enthusiasts of urbanism, architecture, planning, interiors, and the social sciences"--
The Arcade / Pablo Meninato -- The Shopping Mall / Judith De Jong -- The Roman Domus: Interior Urbanism at a Domestic Scale / Helen Turner -- Bedouin Women Sellers and Kuwait's Souk Wajif / Reem J. Dashti and Tasoulla Hadjiyanni -- Sound Mind: Media and Mediations of Interior Soundscapes / Keena Suh -- A Brief Allegory of Capitalism in the Time of Plague / Ed Mitchell.
OCLC-licensed vendor bibliographic record.
Keywords: Space (Architecture) -- Social aspects; Social psychology; ARCHITECTURE / General; ARCHITECTURE / Decoration & Ornament; ARCHITECTURE / Interior Design / General